Pelatihan Penulisan Artikel Ilmiah dan Cara Submit Ke OJS bagi Mahasiswa Program Studi Pendidikan Bahasa Indonesia - da Costa, Romilda Arivina; Somelok, Grace (Universitas Pattimura, 2024)
This community service activity aims to enhance the academic literacy of students in the Indonesian Language Education Study Program, particularly in writing scientific articles and using the Open Journal System (OJS) platform as a publication medium. In practice, many students still face challenges in composing scientific articles that meet academic standards and are unfamiliar with the publication process on OJS. This skill is crucial for fostering an academic culture, supporting final projects, and boosting graduates' competitiveness in academia and the professional world. During offline training, participants were guided from basic understanding of scientific articles, scientific writing rules, to step-by-step technical practices in uploading and submitting articles on OJS. The training consisted of interactive lectures, group discussions, and hands-on simulations led by experienced facilitators. Evaluation results indicated a significant improvement in participants' understanding of scientific article structure and publication procedures on OJS-based journals. Participants also demonstrated high enthusiasm throughout the activities. This training is expected to be the first step toward cultivating a culture of scientific publication among students and inspiring them to share knowledge through scientific journals actively.